Why E-learning as it stands is not enough - Kulathuramaiyer, Narayanan; Maurer, Hermann (Springer, 2011)
E-Learning today has become widely accepted as a means of information and knowledge access and sharing for many learning applications. Despite the extensive growth E-learning systems and contents, it has to be noted that there are still many shortcomings that has led us to ask the question: Is E-Learning as it stands enough? E-Learning as it stands today is far from being assimilated fully into everything that we do. To make things worse, the age of Google is further challenging E-Learning, through the emergence of phenomena such as Google Copy Paste Syndrome, the flattening of expertise, short-spanned learner focus and the emerging culture of mediocrity. The full symbolic power of the emerging Web dragons together with emerging social trends is expected to challenge E-Learning much more in future. This paper then highlights the extent of influence of global Data Mining companies on the current and future E-Learning. A personalized localized control scenario is given to serve as an ideal for making E-Learning to become enough for its envisaged purpose.